Protective role of Bacillus Calmette–Guérin vaccine in Alzheimer's disease progression: A systematic review and meta-analysis - Tungki Pratama Umar; Nityanand Jain; Bella Stevanny; Binish Javed; Andyra Priandhana; Reynold Siburian; Andrejs Kostiks (Heliyon, 2024)
Introduction: Alzheimer's disease (AD) represents a significant societal challenge, highlighting the need to explore effective prevention and treatment approaches. Recent literature has suggested that Bacillus Calmette-Guérin (BCG) vaccine may be a viable therapeutic option for immune disorders associated with AD due to its immunomodulatory properties and protection against various diseases. Methods: This systematic review aimed to evaluate the association of BCG vaccine in the prevention of AD using six medical-scientific databases. A meta-analytical approach was undertaken to estimate the risk of AD incidence in patients with and without BCG vaccine exposure, followed by subgroup analyses. A risk of bias (RoB) assessment was performed using the Newcastle-Ottawa Scale (NOS). Results: Six cohort studies meeting our inclusion criteria were included (47,947 participants) in the study. From our meta-analysis, intravesical BCG vaccine administration lowered the risk of incidence of AD by 26% in non-muscle-invasive bladder cancer (p < 0.00001). Subgroup analyses showed that BCG vaccination showed a potentially notable preventive effect on AD in older adults (>75 years) and female participants. Conversely, significant heterogeneity in results was observed among male participants and those aged <75 years. The RoB was low in three studies and unclear in the remaining studies. Conclusions: Although our results support the potential benefits of BCG vaccine in preventing AD in specific demographics, we remain cautious about interpreting such results. Further research examining the implications of BCG vaccination for prevention and possible treatment of AD should be undertaken in the future.